The Influence of Intellectual Models on Corporate Values With Financial Performance as Intervening Variables - Hairul Anam; Verlia Justine Prabowo (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study attempts to analyse the influence of intellectual capital on firm value with financial performance as an intervening variable. This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange in the period of 2016-2018. This study uses purposive sampling with a total sample of 46 companies. Analysis of the data used is path analysis. The results of this study indicate that Value Added Employed Capital (VACA) and Structural Capital Value Added (STVA) support financial performance, Value Added Human Capital (VAHU) does not support financial performance, The Value Added Capital Employed (VACA) does not affect with the value of the company, the Value Added Human Capital (VAHU) and the Structural Capital Value Added (STVA) affect the value of the company. Financial performance mediates the relationship between intellectual capital and firm value.